2001
DOI: 10.1093/eurpub/11.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and physical demands on caregivers in home care to the elderly in Switzerland and their relationship to nursing home admission

Abstract: Background: Planning the home care of growing numbers of old, dependent people must include the caregivers' burden. Methods: A convenience sample of 129 caregivers of elderly patients with multiple diagnoses was interviewed about the caregiving context, burden, caregivers' tolerance of patients' troublesome behaviours and physical symptoms, mutuality and feelings of closeness between caregiver and patient. Continued maintenance of home care was assessed by a follow-up telephone call. Results: Caregivers were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 25 publications
3
48
0
4
Order By: Relevance
“…Third, sleep problems are a major predictor of subsequent entry into nursing homes (Pollak & Perlick, 1991;Kesselring et al, 2001). Pollak and Perlick (1991) found that 70% of primary caregivers of elders recently admitted to US nursing homes cited nocturnal problems in their decision to institutionalize, primarily because their own sleep was disrupted.…”
Section: Researching Sleep and Caregivingmentioning
confidence: 99%
“…Third, sleep problems are a major predictor of subsequent entry into nursing homes (Pollak & Perlick, 1991;Kesselring et al, 2001). Pollak and Perlick (1991) found that 70% of primary caregivers of elders recently admitted to US nursing homes cited nocturnal problems in their decision to institutionalize, primarily because their own sleep was disrupted.…”
Section: Researching Sleep and Caregivingmentioning
confidence: 99%
“…Giving informal care to a person suffering from stroke with persistent disabilities or from dementia with deteriorating functional and cognitive abilities encompasses a much longer time span than is frequently investigated Kesselring, et al, 2001;). The number of longitudinal studies conducted longer than one year is small.…”
Section: Discussionmentioning
confidence: 99%
“…Research reports predominantly on the negative impacts and consequences . These consequences apply not only in the case of stroke patients but also to other patient groups, who are (progressively) impaired by a chronic disease Kesselring et al, 2001;Thommessen et al, 2002). It is therefore important to be aware of who is providing the care for these patients and how this type of caregiving affects the informal caregiver.…”
Section: Informal Carementioning
confidence: 99%
See 2 more Smart Citations